Comparison of Solid-Phase Extraction Sorbents for Monitoring the In Vivo Intestinal Survival and Digestion of Kappa-Casein-Derived Caseinomacropeptide - Yunyao Qu; Bum-Jin Kim; Jeewon Koh; David C. Dallas (Foods, 2023)
Kappa-casein-derived caseinomacropeptide (CMP)—a 64-amino-acid peptide—is released from kappa-casein after rennet treatment and is one of the major peptides in whey protein isolate (WPI). CMP has anti-inflammatory and antibacterial activities. It also has two major amino acid sequences with different modifications, including glycosylation, phosphorylation, and oxidation. To understand the potential biological role of CMP within the human body, there is a need to examine the extent to which CMP and CMP-derived fragments survive across the digestive tract, where they can exert these functions. In this study, three solid-phase extraction (SPE) methods—porous graphitized carbon (PGC), hydrophilic interaction liquid chromatography (HILIC), and C18 chromatography—were evaluated to determine which SPE sorbent is the most efficient to extract intact CMP and CMP-derived peptides from WPI and intestinal digestive samples prior to LC-MS/MS acquisition. The C18 SPE sorbent was the most efficient in extracting intact CMP and CMP-derived peptides from WPI, whereas the PGC SPE sorbent was the most efficient in extracting CMP-derived peptides from intestinal digesta samples.